Improving Student Participation In History Lectures: Suggestions For Successful Questioning - Pennell, Myra (Teaching History: A Journal of Methods, 2000)
For years I have worked with beginning history and social studies teachers at both the K-12 and college levels. Hundreds of observations have illustrated for me that one of the most difficult and common problems faced by novice teachers is motivating students to participate in lessons. Indeed, the beginner who does not have difficulty with student inertia or even apathy is the exception rather than the rule. Student passiveness is particularly manifest and troublesome when the teacher attempts to use the lecture/discussion technique of instruction so prevalent in history classes. There are two facets to the quandary of how to engage students. First, beginning teachers must sort out confused thinking about the responsibility of both teacher and student for learning. The second is that they must add to their meager beginner's repertoire specific tactics that stimulate student participation.